Macro And Microeconomic Analysis Of Profitability At PT. Bank Bca Syariah - Eka Sutisna; M. Arya Dirgantara; Zaqia, Nurul Zahwa (Indonesian Scientific Publication, 2024)
The purpose of this research is to examine the impact of macroeconomics and microeconomics on profitability at BCA Syariah Bank from 2020 to 2022. Inflation, GDP, and Money Supply are the macroeconomic indicators employed in this study, whereas DAR, DER, and BOPO are the microeconomic indicators. The ROA ratio is utilized as a dependent indication of profitability. This study's population consists of all monthly financial data from BCA Syariah Bank from 2010 to 2023. Using the approach of purposive sampling. The study's sample period lasted from July 2020 to September 2022. The classical assumption test, multiple linear regression, and hypothesis testing are employed as test methods. According to the findings of this study, macro and micro variables both have a substantial impact on profitability (ROA). Inflation, GDP, money supply, DAR, DER, and BOPO variables all have an impact on profitability (ROA). Money supply and BOPO indicators have a considerable impact on profitability (ROA), but inflation, GDP, DAR, and DER have a minor impact.